Aplikasi Bot Telegram Untuk Media Informasi Perkuliahan Program Studi Informatika-Sistem Informasi Bisnis Universitas Kristen Petra - Loren Natasya Gunawan; Justinus Anjarwirawan; Andreas Handojo (Jurnal Infra, 2018)
Sometimes to get information about the lectures, the students are a bit distressed. Often also when it comes to administration, students have not received information about the required lectures. This causes the students to be rarely or even never at all to go to the administration and tend to just wait for information from friends who sometimes can cause miss communication.Seeing the usefulness of bots that can help the work and daily activities of humans, finding information and gathering information, Telegram created a bot named Bot Telegram. With this Telegram Bot can help the administration / lecturers in conveying information about the lectures to students appropriately and quickly. In addition to providing information, in Bot Telegram it can send a file and then download the file. It can also assist lecturers in delivering lecture materials. Lecturers can upload the material into the Telegram Bot then students can download it from the Telegram Bot.This telegram bot application helps the administration and lecturers to convey information to students. Administrative officers are very helpful with the application of this Telegram bot let alone how to use this application is quite.